Physical Monitoring in Swimming Athletes: Leveraging Dominant Physique as a Benchmark - Husein Allsabah, M. Akbar; Putra, Rendhitya Prima; Weda; Sugito; Puspodari; Junaidi, Slamet (GANDRUNG: Jurnal Pengabdian Kepada Masyarakat, 2024)
In swimming, there are several components of physical condition that need to be mastered, while partners do not have data on the physical condition of their athletes as a consideration for providing daily training programs. The purpose of this parameter test is to equip swimming coaches in Kediri City and Regency to be able to find out the physical condition of their athletes at this time so that it becomes the basis for providing training programs that can be right on target. The method used in community service activities is a physical condition test of swimming athletes, the test instrument used there are 10 components of test items, data is analyzed using averages and percentages. The results of community service activities in the dominant results of the analysis of the physical condition of male athletes in cities and districts showed that 60% of male athletes in Kediri city had medium abilities, 45% of male athletes in Kediri district had less abilities. In the women's results, 50% of female athletes in Kediri have medium abilities, 40% of female athletes in Kediri have less abilities. Thus, it can be concluded that the physical condition of male and female athletes in Kediri city has moderate physical condition abilities, while male and female athletes of Kediri regency have less physical condition abilities.